Demand Side Management of a pool of air source heat pumps for space heating and domestic hot water production in a residential district. (1st December 2020) - Vivian, Jacopo; Prataviera, Enrico; Cunsolo, Francesco; Pau, Marco
Highlights: Heat pump management flattens the power profile of residential districts. The heat pump scheduling shifts the load to off-peak periods. Peak shaving results are affected by seasonality and user behaviour. Hot water storage tanks enhance the flexibility of the district. The cost of flexibility is a slight increase of daily start-up events. Abstract: The ongoing electrification of the heating sector will severely affect the patterns of power consumption in electrical distribution systems. Coupling electric heat pumps to thermal energy storage systems allows to increase the flexibility in their operation, thus minimizing the side effects on the electrical grid. This paper investigates the potential of an optimization algorithm that coordinates the operation of a pool of heat pumps in a residential district with the aim of reducing the power peak at grid level. In the simulated scenarios, the heat pumps are coupled to heat storage tanks for space heating and domestic hot water production. The simulations show that the proposed Demand Side Management strategy allows reducing daily peaks up to 21% when only space heating is considered, and up to a 35% when domestic hot water tanks are included in the optimization. The article discusses the effects of different factors, such as weather conditions and user behavior, as well as the uncertainty inherent to the predictions of domestic hot water and electrical consumption. In conclusion, the paper shows that a centralized management of the heat pumps can significantly contribute to reducing the issues linked to the extensive electrification of residential heating systems.